2014
DOI: 10.1037/a0031711
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual and empirical challenges to the “authentic” versus “hubristic” model of pride.

Abstract: An increasingly influential perspective in the study of pride holds that there are two distinct facets characterized by distinct ways of appraising the causes of achievement. "Authentic Pride" has been characterized as attributing success to one's temporary effort, whereas "Hubristic Pride" purportedly attributes success to one's stable, innate ability. In four studies, we present evidence against both predicted attributional profiles, and demonstrate that the Hubristic Pride Scale does not measure feelings of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(145 citation statements)
references
References 54 publications
5
137
3
Order By: Relevance
“…Note that the former motivation for endorsing HP, highlighted in our "Merited Success versus Unmerited Display" (M/U) model, is antithetical to even the most basic conceptions of pride, for which attributing achievement to oneself is criterial (Tracy & Robins, 2007). Across several studies (Holbrook, Piazza, & Fessler, 2014; see also the study below), we document a pattern in which overclaiming credit for success increases HP ratings, and HP ratings are either uncorrelated or negatively correlated with attributing success to internal causes. The second motivation for endorsing HP-acknowledging that pride is excessively displayed-can, but need not, indirectly relate to inner feelings of pride.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…Note that the former motivation for endorsing HP, highlighted in our "Merited Success versus Unmerited Display" (M/U) model, is antithetical to even the most basic conceptions of pride, for which attributing achievement to oneself is criterial (Tracy & Robins, 2007). Across several studies (Holbrook, Piazza, & Fessler, 2014; see also the study below), we document a pattern in which overclaiming credit for success increases HP ratings, and HP ratings are either uncorrelated or negatively correlated with attributing success to internal causes. The second motivation for endorsing HP-acknowledging that pride is excessively displayed-can, but need not, indirectly relate to inner feelings of pride.…”
mentioning
confidence: 84%
“…Tracy and Robins also express concern that our correlational studies focus exclusively on trait rather than state measures of AP and HP (Holbrook et al, 2014, Studies 2 and 3), as event-based appraisal antecedents are inherently related to evocations of state affect. We agree that the lack of state measures presents a significant gap in the data we have presented, and have therefore conducted a new study in which participants recalled an important achievement, reported their state AP and HP, appraised the causes of their achievement, rated the degree to which they felt genuinely deserving of credit for their life success in general, and rated their propensity to outwardly display pride to others.…”
Section: State Versus Trait Affect and Appraisal Antedecentsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is another stage where feeling pride happens: One cannot, for example, choose to be the child of someone important, but it is adaptive for the person to recognize the way this attribute increases how others value them. Assimilating this heightened valuation or deference allows individuals to pursue social opportunities previously beyond reach (7,29,30) or to press for better treatment from others (32).…”
Section: The Advertisement-recalibration Theory Of Pridementioning
confidence: 99%